(3eLehY COHjs
(3ChdgG (B:s
(3bjd aj SfI CKfJjf hNeSjf hKdGK eFI bOe Edi fGUQ GdOhdI QLdGf ef GdCQef eJdUbGf SfgeG NeS (B((3hYTQjf(B) (3SfI s
(3BNQgG (B:s
(3aCNHQhg Cfg ehSi Hf GdQVG Hf LYaQ GdUGOb (B((3V(B)(3, hYf MSHg hfSHg hYf LejY GdBd s
(3ajg McGjGJ hfhGOQ hZjQgGs
(3hHgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B185 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs